Optimization and Performance Evaluation of Microchannel Heat Sinks for High-Power Density Applications (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
Microchannel heat exchangers have been the subject of theoretical investigation. The exchanger's thermal behaviour is predicted by solving the equations of the computational fluid dynamics (CFD) model. Problem geometry and meshing were done in ANSYS Workbench. The models have been solved using the ANSYS Fluent 12.0 solver. This profile is made to fit four distinct geometries. Their shapes are V-shaped, rectangular, convergent, and divergent. The coolant fluid in this case is distilled water. After comparing the present CFD estimated heat transfer coefficient value with the analytical results, it was found to be quite close. The findings demonstrate that in both turbulent and laminar zones, the heat transfer coefficient is enhanced by the addition of distilled water. This study proves the relationship between the heat transfer coefficient and the fluid's thermal conductivity, denoted as h α k. A rectangular microchannel's hydrodynamics and thermal behaviour are examined in this work. Calculations made using ANSYS Fluent for wall temperature change, channel pressure drop, and friction factors provide good predictions for the experimental data. Using pressure, temperature, and velocity contours, its behaviour has also been studied.